The Effect of Microgravity-Like Conditions on High-Level Cognition: A Review - Mammarella, Nicola (Frontiers in Astronomy and Space Sciences, 2020)
With an increasing interest in space travelling, the potential risks and benefits of microgravity on mental functioning is becoming a central research issue. Here we briefly reviewed a series of behavioral studies in order to identify what is known and not known about the effects of microgravity on higher cognitive functions. We first used a general approach to describe the interaction between microgravity and higher cognition. Subsequently, we analytically described a series of studies that focused on single high-level cognitive processes (e.g., mental imagery, working memory, etc.). Altogether, these findings point to a complex pattern of data mainly explained by the variety of methodological aspects (e.g., duration of microgravity-like conditions, low number of studies.). Even so, the importance of higher-level cognitive functions for space performance remains fundamental and deserves further attention. These data are ultimately interesting in light of the potential long-term effects that microgravity may play on return to Earth.